2014
DOI: 10.1088/0953-8984/26/6/064201
|View full text |Cite
|
Sign up to set email alerts
|

A comparison ofτ-MnAl particulates produced via different routes

Abstract: MnAl alloys are very promising rare-earth-free permanent magnets. Nanocrystalline microstructures can have beneficial effects on the properties of magnetic MnAl alloys. In the present work we examined multiple routes to process MnAl alloys and studied the effects of milling on Mn-46 at.% Al powders. Mn54Al46 was produced via gas atomization, melt spinning, and rapid solidification rate processing. It was then mechanically milled using a water-cooled Union Process attritor for times up to 20 h. X-ray diffractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 30 publications
1
19
1
Order By: Relevance
“…Ball milling is a well-known technique used for microstructure refinement and strain inducement, but also for promotion of metastable phase formation. Previous studies show that high coercivities (above 4 kOe) can be achieved in MnAl after milling for a typical time duration of several to dozen of hours [20,21,24,25]. A coercivity of 5.3 kOe has been recently reported by Lu et al [26] in isotropic MnAl powders by starting with melt-spun ribbons, annealing at 410 ºC for 30 min and subsequent milling for 23 hours.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Ball milling is a well-known technique used for microstructure refinement and strain inducement, but also for promotion of metastable phase formation. Previous studies show that high coercivities (above 4 kOe) can be achieved in MnAl after milling for a typical time duration of several to dozen of hours [20,21,24,25]. A coercivity of 5.3 kOe has been recently reported by Lu et al [26] in isotropic MnAl powders by starting with melt-spun ribbons, annealing at 410 ºC for 30 min and subsequent milling for 23 hours.…”
Section: Introductionmentioning
confidence: 94%
“…The structure and magnetic properties of the MnAl system have been widely studied because the microstructural changes and defects introduced during the metastable -phase transformation highly influence its magnetic properties. Studies have reported various techniques to prepare MnAl-based alloys, including hot extrusion, melt spinning, mechanical alloying, mechanical milling (MM), cryomilling, and gas-atomization [8,9,[17][18][19][20][21][22][23]. Ball milling is a well-known technique used for microstructure refinement and strain inducement, but also for promotion of metastable phase formation.…”
Section: Introductionmentioning
confidence: 99%
“…3 Addition of a small amount of C slows down the decomposition of the τ-phase and increases H c . 4 Various techniques such as mechanical milling, 7,8 mechanical alloying, 9,10 melt-spinning, 11,12 gas atomization, 13 spark erosion 14 were used to make base material (powder) which then was consolidated to make bulk magnets by spark plasma sintering 15 and equal channel angular extrusion. 16 Unfortunately, all the results reported so far are very inferior compared to the properties reported by Ohtani et al 4 Though the powders exhibited high coercivity (>4.8 kOe), 17 the magnetization was significantly lower and the consolidated bulk magnets showed a further decrease in magnetization and coercivity as well.…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques have been used to prepare Mn-Al based permanent magnets, including hot extrusion, mechanical alloying, melt-spinning, gas atomization and mechanical milling, etc [10][11][12][13][14][15]. Highly anisotropic Mn-Al magnets were prepared by hot extrusion technique, with M r of 93 Am 2 kg À1 , l 0i H c of 0.3 T [16].…”
Section: Introductionmentioning
confidence: 99%